Growth Mindset in Adult Learning: Systematic Literature Review - Soo Jeoung Han; Vicki Stieha; Emily Poitevin; Tina L. Starnes (Adult Education Research Conference, 2018)
We conducted a systematic literature review on mindsets to understand how a growth mindset is conceptualized and investigated in adult learning scholarly work.
Keywords: growth mindset; individual mindset; team mindset; organizational mindset; implicit person theory